Avaliação de métodos de extração de carotenoides produzidos a partir de cultivo submerso - Lima, Mirelle Dayanne Freire de (2023)
The growing interest in the microbiological production of carotenoids to be carried out industrially occurs due to a concern about the use of additives in food and pharmaceutical products. Thus, the interest in low-cost and natural production through biotechnological procedures stood out. Yeasts are focused on because of their protein source, good growth efficiency on low-value substrates and high sugar levels. The yeast Rhodotorula glutinis is capable of synthesizing compounds of industry-wide interest, such as lipids, carotenoids and enzymes, or which generate various specific and economic profits in biotechnological processes. Thus, this work evaluated the efficiency of different methods of carotenoid destruction from Rhodotorula glutinis in synthetic and Manipueira media. First, three different types of rupture were carried out (lactic acid, glass beads and ultrasonic bath), then total carotenoids were filtered using two chemical solvents (hexane and petroleum ether), and finally the use of vegetable oils (sunflower and soy). The efficiency of the carotenoid removal methods was evaluated by absorbances in a spectrophotometer to describe the carotenoid profiles obtained. The selection of the rupture method as well as the carotenoid destruction method is essential, due to the presence of physical and chemical barriers. Therefore, the hexane solvent showed a better concentration of carotenoids using glass beads as cell disruption in the synthetic medium (126,86 μg/g). In extraction with vegetable oil, the best result obtained was using soybean oil in a synthetic medium (18,65 μg/g).